O ensino-aprendizagem de inglês na escola pública paulista: o papel da gramática em proposta pedagógica para o 6º ano - Martinez, Fernanda Cristina Terruggi (2011)
The main purpose of this study is to discuss the controversial grammar teaching role in a student s textbook and in the teacher s guide that follows it, as well as in its methodological orientations. This analysis is carried out taking into consideration the possibility of adapting some of the proposed activities based on grammar as a skill teaching theories. The textbook under analysis is part of a book series which has been developed by the state of Sao Paulo for its sixth year students of public schools. First, we present a discussion about Language Teaching Approach, as well as about Method and Technique according to Anthony (1963), Richards and Rodgers (2002) and Almeida Filho (2003). We also discuss the role of grammar teaching in some of the main foreign language teaching periods, such as Grammar- Translation, Audiolingualism and Communicative Approach. These discussions are aimed at providing a broad understanding of grammar teaching roles so that contemporary grammar teaching theories, such as the grammar as a skill teaching theories by Batstone (1994) and by Larsen-Freeman (2003), could help us illustrated alternative ways of teaching the structures presented in the textbook in question. It seems that these contemporary theories have contributed to the development of activities that may help preteen students take notice of grammar structures through extensive meaningful practice and reflection opportunities. We believe these illustrations may also help students become more autonomous in their learning.